Pemanfaatan Canva Sebagai e-Katalog Dalam Meningkatkan Visibilitas Dan Kehadiran Toko Zaidan di Dunia Digital - Alfandi, Moh.; Ribie, Maya Fransiska; Fitria, Maula Lailatul; Wahyuni, Meyla Tri; Zunaidi, Arif; Mochamad Alvido Zakaria; Hidayah, Islamiati (Welfare : Jurnal Pengabdian Masyarakat, 2023)
This service aims to increase accessibility and convenience for consumers when shopping for products from micro, small, and medium enterprises (MSMEs) through the use of the Canva platform as an e-catalog. The service method includes training and assistance for MSMEs in using Canva to create interesting and informative e-catalogs. Apart from that, consumers are also given a guide to using the e-Catalog to make it easier for them to choose and order products. The results of this service show a significant increase in the accessibility of MSME products via digital platforms. Consumers can easily access the e-catalog, browse products, and make transactions online. MSMEs also experience increased sales and exposure through the use of this technology. In this way, this service has succeeded in expanding market reach for MSMEs and making it easier for consumers to shop for local products. This initiative promotes the growth and sustainability of MSMEs in today's digital era.